Tremors: New Fiction by Iranian American Writers By Anita Amirrezvani and Persis Karim, eds. (Fayetteville: The University of Arkansas Press, 2013. 338 pages.) (American Journal of Islam and Society, 2014)
This collection of short stories and novel excerpts is the first of its kind to appearin English. Its twenty-seven stories are intended for the general publicinterested in exploring new horizons in fiction, although the fact that the bookis published by a university press might limit public access.Tremors is a collection of fiction revolving around the ideas of migration,exile, hybrid identities, and coming to terms with these. The book is dividedinto three sections, each of which, according to the editors, revolves around acentral theme. The stories in the first section, “American Homeland,” involvefictional accounts of the challenges of “immigration and assimilation in theUnited States” (p. xii). This, in fact, is not always the case. In Dena Afrasiabi’s“String,” for example, the female narrator, Forugh, is at home in the UnitedStates, for the only challenges facing her are the memory of her dead motherand the shadow of her sorrow-stricken Iranian father lurking in the background.Similarly, in Salar Abdoh’s “Fixer Karim,” it is the immigrant HeavyK who continues to ease past assimilation barriers in the United States, to theastonishment of the well-established Iranian-American narrator, so much sothat the story ends with Heavy K appearing as the lead singer in a countryband. In a number of stories, (e.g., Taha Ebrahimi’s “Family Trouble” or J.Kevin Shushtari’s “The Sweet Dry Fruit of the Lotus Tree”), in fact, the narrator’sfamily is well established and feels at home, sometimes with an Americanparent, until ghosts or guests from Iran upset the peace.The second section, “Iran, Land of Resilience,” has been so named becausethe setting of these stories is Iran, although not all of them entertainsuch a view about the land. One example is the excerpt from Zohreh Ghahremani’sSky of Red Poppies, in which the dark days of oppression under the ...